Hygrothermal degradation effects on a rubber toughened WPC. (2020) - Mazzanti, V.; Cavalcoli, V.; Balbo, A.; Mollica, F.
Abstract: In recent years, the growing sensibility about environmentally friendly products has pushed the Wood Polymer Composites (WPC) market along an increasing trend. On the other hand, the presence of the wood flour determines a few problems, two of which are particularly significant. First, WPC products are often used in a large range of temperature and moisture conditions that can be demanding for the material. Further, large quantities of wood filler promote the embrittlement of the composite and often cause failure in the finite products. The aim of this work was to evaluate the hygrothermal degradation effects on the tensile properties of a polypropylene based WPC toughened with a thermoplastic elastomer. Santoprene improves the elongation at break, as revealed by tensile tests, but increases porosity, as shown by SEM analysis. In wet conditions, the presence of the thermoplastic elastomer reduces the negative effect of the hygrothermal degradation. For these reasons, the addition of Santoprene is suggested only for applications in humid environment.